Randomised, non-inferiority, controlled procedural outcomes TrIal comParing reverse T And Protrusion versus double-kissing and crush stenting: protocol of the TIP TAP I randomised trial. Issue 6 (16th June 2020) - Rakhimov, Kudrat; Buono, Andrea; Anadol, Remzi; Ullrich, Helen; Knorr, Maike; Ahoopai, Majid; Münzel, Thomas; Gori, Tommaso
Abstract : Introduction: To assess the impact of 'reverse T and Protrusion' (TAP) technique on the outcome after stenting of true bifurcation lesions of the left main (LM) or proximal epicardial vessels as compared with double kissing (DK)-crush technique. Methods and analysis: 50 consecutive patients with true coronary bifurcation lesion (Medina 1, 1, 1 or 0, 1, 1) of the LM or the proximal main vessels, requiring a two-stent technique as first-line strategy at University Medical Center Mainz, are randomised in a 1:1 ratio to reverse TAP or DK-crush stenting. As recommended by best clinical practice, final angiographic result is evaluated and optical coherence tomographic (OCT) intracoronary imaging is performed to assess and optimise the final result. The primary end point is defined as the percentage of stent expansion in the side branch. Secondary end points consist of angiographic and procedural success (assessed until patient's discharge), procedural parameters (procedural time, fluoroscopy time, use of devices, X-ray dose) and OCT parameters expressing expansion of the stents. Safety parameters include all adverse events up to 6 months after discharge. A clinical, angiographic and intracoronary imaging control at 6 months is planned. Ethics and dissemination: The protocol complies with good clinical practice and the ethical principles described in the Declaration of Helsinki and is approved by the local ethics committee. The results of the trial will be published as original article(s) in medical journals and/or as presentation at congresses. Trial registration number: ClinicalTrials.gov Registry (NCT03714750 )